Analisis Sistem Informasi Akuntansi Persediaan Bahan Baku untuk Meningkatkan Efektivitas Pengendalian Internal (Studi Kasus pada Rocket Chicken Baureno Bojonegoro) - Widya, Kiki Purna; Hamid, Abdul; Rika (PUTRA JAWA PUBLISHER, 2025)
This study is intended to analyze the application of an accounting information system for raw material inventory in increasing the effectiveness of internal control at Rocket Chicken Bojonegoro. This research is located on Jl. Ahmad Yani, Ngrandu, Baureno, Bojonegoro, Bojonegoro Regency, East Java 62192. This research was conducted using a qualitative analysis method with a descriptive approach, namely an analysis based on a description that supports the analysis by focusing on an understanding of problems in social life only and detail which only describes the form of sentences.the raw material inventory accounting information system implemented by rocket chicken bourno bojonegoro is running well because it has carried out the provisions in accordance with the raw material inventory procedures. inspection of raw materials regularly and more closely so that there are no delays in recording any existing inventory processes. The accounting information system for raw material inventory at Rocket Chicken Bojonegoro can improve the effectiveness of intemal control.